In vitro evaluation of the quality of obturation with capillary condensation technique and hybrid technique in teeth with simulated internal resorption cavity: A cone-beam computed tomography study - Girija S Sajjan; K Durga Prasad Naik; K Madhu Varma; Sai Lakshmi Durga Indukuri; Atchyut Kumar Gajja; B V Sindhuja (Wolters Kluwer Medknow Publications, 2023)
Aim: The quality of obturation with recent capillary condensation technique and hybrid technique in teeth with artificial internal resorption cavity needs to be evaluated. Methods: Calculation of sample size was done with G*Power software (version 3.1.9.4) (effect size d = 1.46). Eighteen single-canal mandibular premolars were decoronated at the cementoenamel junction for standardization of specimen length as 12 mm. Biomechanical preparation was done with ProTaper Universal rotary file up to F4. Internal resorption cavity was prepared with #08 size round bur 6 mm from the apex. Samples were distributed randomly into two groups. Group I: teeth with bioceramic sealer (EndoSequence BC Sealer, Brasseler, USA) application using conventional technique and hybrid technique of obturation. Group II: capillary condensation technique of bioceramic sealer (EndoSequence BC Sealer, Brasseler USA) using single-cone gutta-percha obturation. The voids in three segments of the root canal were measured with cone-beam computed tomography using "OnDemand3D App" software. Data were statistically analyzed by one-way analysis of variance (ANOVA) and multiple comparisons of Tukey honestly significant difference tests with P < 0.05. Results: The mean area of the void was 0.3963 ± 0.3299 mm2 for Group I and 0.4022 ± 0.4101 mm2 for Group II. There was a difference in the number of voids present in different sections of the root within a group with significance but not between the groups. Conclusion: Capillary condensation technique with single-cone obturation is comparable to conventional sealer application and hybrid technique of obturation for filling internal resorption cavity.